ANALYZING ECOLOGICAL INTERACTIONS OF MARINE ORGANISMS FOR LOCAL ENVIRONMENT-BASED ANIMAL ECOLOGY LEARNING - Aulia Azmi; Rusnizar Rusnizar; Asyifa Umaira; Hanifah Fakhirah; Nadia Aldyza (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
Animal ecology learning in biology education remains predominantly theoretical and often overlooks the potential of local environments as authentic learning resources. Addressing this gap, the present study analyzes the ecological relationships among marine biota based on field observations and explores their potential to support context based animal ecology learning. This study employed a descriptive qualitative approach complemented by quantitative data. Data were collected through field observations using the belt transect method across three observation lines in the coastal area of ​​Beurawang, Sabang. The data were analyzed descriptively to identify marine biota, examine their ecological roles, and relate these findings to key concepts in animal ecology learning. In addition, Spearman correlation analysis was applied to examine relationships among species. The findings identified five dominant marine biota groups, namely sea stars (Linckia laevigata), sea urchins (Echinoidea), nudibranchs (Nudibranchia), coral reefs (Anthozoa), and giant clams (Tridacna sp.), each contributing differently to the coastal ecosystem. The correlation analysis revealed significant positive associations among several species, with coral reefs acting as a central component that strongly influences the presence of other organisms. This indicates that coral habitat structure plays a crucial role in shaping the distribution and stability of benthic communities. Importantly, the study highlights that field based ecological data offers strong potential as meaningful learning resources. The empirical findings can be integrated into instructional practices to support the teaching of ecological concepts such as species interactions, trophic relationships, adaptation, and ecosystem balance in a more contextual and relevant manner. This study therefore contributes to bridging the gap between ecological field research and biology education by promoting the use of local environmental contexts in learning.